2019
DOI: 10.12691/ajnr-7-5-3
|View full text |Cite
|
Sign up to set email alerts
|

Level of Stress and Coping Strategies among Nursing Students at Damanhour University, Egypt

Abstract: Stress has been recognized as a 20th century disease and donates to health problems worldwide, nursing students are exposed to numerous stressors during their studies and clinical training. Determining stress and coping strategies among them will have significant consequences for the nursing career. Aims: to illustrate level of stress and identify coping strategies among nursing students at Damanhour University, Egypt. Research design: A descriptive cross-sectional study was used. Setting: the study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Stress is not a singular facet, but rather arises due to influencing factors that affect the individual and, in turn, impact their response in such situations. For example, one of these stressful situations can occur during students’ clinical practice once the students face a new environment and establish new relationships with staff nurses, patients, and an instructor and/or supervisor [ 18 ]. A study found that the most stressful clinical settings identified by the study were the intensive care unit followed by the emergency room, then the surgical units, while the area that was considered the least stressful was the medical units [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stress is not a singular facet, but rather arises due to influencing factors that affect the individual and, in turn, impact their response in such situations. For example, one of these stressful situations can occur during students’ clinical practice once the students face a new environment and establish new relationships with staff nurses, patients, and an instructor and/or supervisor [ 18 ]. A study found that the most stressful clinical settings identified by the study were the intensive care unit followed by the emergency room, then the surgical units, while the area that was considered the least stressful was the medical units [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the third and final theme, nursing students in clinical training are unable to avoid stressors and must learn to cope with or adapt to them. Previous research has reported a link between stressors and the coping mechanisms used by nursing students [51][52][53]. In particular, the inability to manage stress influences nurses' performance, physical and mental health, attitude, and role satisfaction [54].…”
Section: Discussionmentioning
confidence: 99%
“…A p value of .021 was found in the correlation of students who face stress due to inability to achieve their desired grades, and also experience stress due to high parental aspirations, which coincides with the results of a study conducted in India. 17 The reason might be that students perceive their parental aspirations to be stressful, making them want to achieve the maximum, within a limited time period, which often causes stress among them.…”
Section: Discussionmentioning
confidence: 99%